1989
DOI: 10.1007/bf00442557
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related plasma levels of clozapine: influence of smoking behaviour, sex and age

Abstract: Drug monitoring in psychiatry is of increasing interest due to compliance problems, side effects of psychoactive drugs and the search for adequate dosage. In the present study, plasma levels of clozapine, as determined by high performance liquid chromatography, were investigated in 148 patients receiving a daily dose between 12.5 and 700 mg clozapine. Regression analysis revealed a linear relationship between dose and plasma concentrations. Plasma concentrations at a given dose (level divided by dose and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
3
4

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(91 citation statements)
references
References 6 publications
8
76
3
4
Order By: Relevance
“…Haring et al [34] found that clozapine concentrations in patients aged between 45 and 54 years were higher than that in patients aged between 18 and 26 years, but the effect was not statistically significant. Another recent study without smoking information demonstrated there was a negative effect of age on the clearance of clozapine [15] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Haring et al [34] found that clozapine concentrations in patients aged between 45 and 54 years were higher than that in patients aged between 18 and 26 years, but the effect was not statistically significant. Another recent study without smoking information demonstrated there was a negative effect of age on the clearance of clozapine [15] .…”
Section: Discussionmentioning
confidence: 97%
“…Because the activity of CYP1A2 is greater in smokers than in non-smokers [9] , the clearance of clozapine is likely influenced by smoking status. It was reported that smoking can increase the clearance of clozapine and that the sudden cessation of smoking can cause a significant decrease in caffeine clearance (P<0.01) of 36.1% [32][33][34] . Sex was also reported to be a significant covariate affecting the clearance of clozapine and norclozapine [11,35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, we showed that phenacetin was a weak inhibitor of the formation of all three theophylline metabolites. Furthermore the neuroleptic drug, clozapine, a putative substrate for CYP1A2 [40][41][42][43], was also a weak inhibitor of the three major pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown for haloperidol (Jann et al, 1986) and tacrine (Zevin and Benowitz, 1999). Other examples are: fluvoxamine levels in smokers are 1/3 that of nonsmokers (Spigset et al, 1995), clozapine levels are 1/3 lower for men, 1/5 for women compared with nonsmokers (Haring et al, 1989), and smoker olanzapine levels are 1/5 that of nonsmokers (Carrillo et al, 2003). Clearly cessation of smoking can cause "overdose" toxicity for a patient taking any of these medications and then stops smoking.…”
Section: Polycyclic Hydrocarbons and Drug Metabolism 11mentioning
confidence: 94%